Sistem Informasi Penanganan Keluhan Pelanggan di Rumah Sakit Umum Surya Husadha Denpasar Berbasis Web - Dewa putu yudhi Ardiana; I Made Shaja Dwiputra (Universitas Bumigora, 2019)
The hospital as one of the largest health installations always strives to implement quality services because it has an impact on customer satisfaction and brings in new customers. Customer complaints that are not handled properly will adversely affect the impression of the hospital. The difficulty faced by Surya Husadha General Hospital Denpasar is handling customer complaints that are still manual by wrote to the paper. This method is considered not maximal in efforts to provide handling and managing customer complaints. The purpose of this research is to build an information system for handling customer complaints that can help hospital customer care in managing customer complaints, confirm complaints to the relevant units and validate the actions taken. Customer complaint handling information systems can also produce complaints information that has been handled and has not been handled as well as customer complaints reports based on certain time units. The results of the research indicate that it has succeeded in building a complaints information system that can help customer care in managing customer complaints. The results of black box testing show that the system functions run well.